The Role of Self-Control and Fintech Trust in Strengthening the Impact of Digital Financial Literacy On Sustainable Financial Behavior : a Study of Millenial Fintech Users In South Kalimantan - Nurul Hasanah; Farida Yulianti; Jose Da Silva; Juvenal Da Costa; Tri Ratnawati (International Journal of Economics, Management, Business, and Social Science (IJEMBIS), 2026)
The rise of digital transformation in the global financial landscape has reshaped how people manage, store, invest, and spend their money. Indonesia, as one of the most rapidly developing nations in Southeast Asia, has experienced a notable growth in the utilization of financial technology (fintech). Within this development, the millennial generation represents the largest group of fintech users, yet they also remain highly susceptible to poor and unsustainable financial practices. This study aims to examine how digital financial literacy impacts sustainable financial behavior, incorporating self-control as a mediating factor and fintech trust as a moderating factor. A quantitative method was applied using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the SmartPLS 3.2.9 software. Data were gathered from 250 millennial fintech users located in South Kalimantan. The results reveal that digital financial literacy significantly improves sustainable financial behavior, both directly and indirectly through the role of self-control. However, fintech trust does not significantly moderate this relationship. These results broaden the application of Behavioral Finance Theory by highlighting that digital financial behavior is shaped not only by rational economic decision-making but also by psychological aspects such as self-regulation and trust in fintech systems. The study offers empirical insights into digital financial literacy in developing economies and provides practical recommendations for policymakers and fintech companies to strengthen digital financial education and public trust strategies.